The effect of problem-based learning on students teamwork ability in UiTM Trengganu, Malaysia - Adnan, Noor Liza; Wan Abdullah, Wan Karomiah; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
One of the criteria looked for by the employers in employing a staff is the ability to work in a team, especially when employees of an organization could come from diverse background and culture as a result of globalization. However, many of our graduates do not possess this ability, which later contributes to poor work performance. Many parties blame the higher institutions as they fail to expose the students to real working environment, since the teaching method used is more centered on delivering knowledge without inviting active participation from the students. Hence, this paper attempts to examine whether Problem-Based Learning (PBL) would give positive effects to teamwork ability (TWA) and to determine whether students of different gender and CGPA would evaluate TWA differently. A preferred learning approach was also sought. The respondents consisted of 48 graduating accounting students from UiTM Terengganu. It was discovered that PBL did affect teamwork ability as measured by Paired Samples t-Test before and after the PBL session. They felt that their teamwork ability had been enhanced after a semester of PBL. Independent Samples t-Test showed that both genders did not differ significantly in their views of TWA as a result of PBL. However, students with lower CGPA of below 3.00 felt that PBL had improved their TWA better than students with higher CGPA of 3.00 to 3.49. When further probed, many preferred a combination of PBL and lecture approach rather than learning solely based on lecture. However, this study was conducted on a rather small sample size which limits the scope of the study. Hence, another study which uses bigger sample size, across the whole UiTM campuses and various faculties would give a better picture on the effect of PBL on TWA. Comparison with other universities implementing PBL would provide a more holistic result.